1991
DOI: 10.1002/mus.880140902
|View full text |Cite
|
Sign up to set email alerts
|

AAEM minimonograph #14: The influence of temperature in clinical neurophysiology

Abstract: AAEM MINIMONOGRAPH # 14 Temperature affects biologic and neurophysiologic processes and is, therefore, always well controlled in in vitro experiments. Its role is equally important in the clinical laboratory but has often been neglected. Lower temperature cause slower nerve conduction velocities (NCVs), and increased amplitudes of muscle and nerve potentials. Fibrillations may disappear, and muscle contraction will be slower and weaker. Neuromuscular transmission improves. Somatosensory evoked potentials (SEPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
3

Year Published

1992
1992
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(90 citation statements)
references
References 86 publications
4
83
0
3
Order By: Relevance
“…Whereas studies in other sensory nerves observed a decrease in the SCV 18,[22][23][24] , an increase in the SDL 18,25,26 , and an increase in the SNAP amplitude 24,27 when the temperature is reduced. Our findings of absence of effects of temperature on the DUC nerve conduction are probably the result of narrow temperature variation allowed during the entire test as part of our method of investigation.…”
Section: Discussionmentioning
confidence: 79%
“…Whereas studies in other sensory nerves observed a decrease in the SCV 18,[22][23][24] , an increase in the SDL 18,25,26 , and an increase in the SNAP amplitude 24,27 when the temperature is reduced. Our findings of absence of effects of temperature on the DUC nerve conduction are probably the result of narrow temperature variation allowed during the entire test as part of our method of investigation.…”
Section: Discussionmentioning
confidence: 79%
“…The hand temperatures still ranged, however, between 29.0 and 36.2"C (mean 33.3"C) for the dominant hands and between 29.0 and 36.0°C (mean 33.2"C) for the nondominant hands. The influence of hand temperature on the absolute electrophysiological results is well known (26). In this study, however, relative electrophysiological findings (the difference between the ipsilateral median and ulnar sensory peak latencies) were examined rather than absolute values.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature is one of the most important factors influencing nerve conduction parameters [8][9][10][11][12] . L a t e n c y, amplitude, duration and area of the sensory nerve and compound muscle action potentials increase as the temperature falls.…”
Section: Influence Of Temperature On Comparative Nerve Conduction Tecmentioning
confidence: 99%